2017
DOI: 10.1098/rspb.2017.1000
|View full text |Cite
|
Sign up to set email alerts
|

Odours from marine plastic debris induce food search behaviours in a forage fish

Abstract: Plastic pollution is an anthropogenic stressor in marine ecosystems globally. Many species of marine fish (more than 50) ingest plastic debris. Ingested plastic has a variety of lethal and sublethal impacts and can be a route for bioaccumulation of toxic compounds throughout the food web. Despite its pervasiveness and severity, our mechanistic understanding of this maladaptive foraging behaviour is incomplete. Recent evidence suggests that the chemical signature of plastic debris may explain why certain specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 45 publications
2
67
0
Order By: Relevance
“…In the summer of 2015, I tested this question on Northern Anchovy (Engraulis mordax), an ecologically critical forage fish species and known plastic consumer (2). Anchovy responded to odors of food and plastic debris similarly, increasing clustering behavior and reducing school-wide rheotaxis in a manner that is characteristic of olfactory search (12). These behaviors are consistent with foraging in this species.…”
Section: The Ecology Of An Olfactory Trapsupporting
confidence: 58%
“…In the summer of 2015, I tested this question on Northern Anchovy (Engraulis mordax), an ecologically critical forage fish species and known plastic consumer (2). Anchovy responded to odors of food and plastic debris similarly, increasing clustering behavior and reducing school-wide rheotaxis in a manner that is characteristic of olfactory search (12). These behaviors are consistent with foraging in this species.…”
Section: The Ecology Of An Olfactory Trapsupporting
confidence: 58%
“…Savoca et al () hypothesized that the odor of dimethyl sulfide‐related chemicals that accumulated on plastics increased their consumption by sea birds. Savoca et al () later observed that aqueous leachates generated from weathered/biofouled polypropylene beads resulted in foraging behavior in the northern anchovy ( Engraulis mordax ) mimicking that observed when extracts of food were provided. Exposure to unfouled beads did not elicit such a response.…”
Section: Fate Of Microplastics In the Oceanmentioning
confidence: 99%
“…Other studies have demonstrated that biofilm formation is not essential to increase the attractiveness of microplastic to marine grazers, such as copepods; microbeads spiked with DMS were sufficient to induce selective feeding in copepods (Procter et al ). In addition, olfactory mechanisms were also implicated to activate the ingestion of plastic debris by fish (Savoca et al ).…”
Section: Microorganisms Mediate Microplastic Exposure and Impacts In mentioning
confidence: 99%